Structure of fish communities in relation to habitat in Matusagaratí Lagoon, Darién, Panama - Valdés-Díaz, Samuel (2025)
Introduction: Matusagaratí lagoon is an ecosystem with diverse habitats and environmental conditions that determine the diversity and distribution of aquatic life. Despite hydraulic connectivity, aquatic habitats generated by this diversity of environmental conditions could determine the composition and structure of fish assemblages. Objective: To understand the structure of fish community in three of these habitats. Methods: Multi-habitat sampling was conducted between March 2022 and September 2023, covering periods of drought and flooding, at 29 sites using different fishing techniques. Results: 1 913 fish from 50 species and 27 families were collected in approximately 320 km2. Three fish assemblages were identified, each associated with a specific habitat. The river corridor of the Tuira River had the greatest diversity, followed by the tidal streams and lagoons. Conclusions: The analysis revealed notable differences between these habitats, with the river corridor dominated by peripheral species, while lagoons showed low diversity with generalized or hypoxia-adapted species. The presence of species such as Hoplosternum punctatum, Ageneiosus pardalis and Pimelodus punctatus in the wetland evidences the influence of the Choco region on Panama´s ichthyofauna. These findings could have important implications for the formulation of wetland conservation strategies.